Cardiorespiratory Fitness Levels in Coronavirus Disease Survivors - Puja Asmaul Husna; Riskah Nur’amalia; Meutia Mutmainnah (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2023)
Introduction: Covid-19 survivors often complain of fatigue, cough, shortness of breath, fever, dermatitis, headache, etc. This decrease then has an impact on changes in cardiorespiratory fitness. Objective: Determine the level of cardiorespiratory fitness in Covid-19 survivors. Method: This study used a cross-sectional design. The population of this study is Covid-19 survivors in Makassar City. Sampling using purposive sampling technique with a sample of 385 people. Data collection was carried out by taking primary data by measuring cardiorespiratory fitness levels using the Six Minute Walk Test (6MWT). Results: A total of 236 people (61.3%) of Covid-19 survivors had a low level of cardiorespiratory fitness with an average distance value of 507.6 meters. Conclusion: Respondents from the adolescent age group have a normal BMI, high activity, asymptomatic and mild symptoms, and a phase of chronic Covid-19 infection tend to have a good level of cardiorespiratory fitness. While most respondents from the elderly age group, who have obese and obese BMI, work as medical personnel with low physical activity, accompanied by comorbidities, and the acute Covid-19 infection phase has a low level of cardiorespiratory fitness.